A Theoretical Framework for Soft-Information-Based Synchronization in Iterative (Turbo) Receivers. Issue 2 (28th April 2005) - Noels, Nele; Lottici, Vincenzo; Dejonghe, Antoine; Steendam, Heidi; Moeneclaey, Marc; Luise, Marco; Vandendorpe, Luc
Abstract : This contribution considers turbo synchronization, that is to say, the use of soft data information to estimate parameters like carrier phase, frequency, or timing offsets of a modulated signal within an iterative data demodulator. In turbo synchronization, the receiver exploits the soft decisions computed at each turbo decoding iteration to provide a reliable estimate of some signal parameters. The aim of our paper is to show that such "turbo-estimation" approach can be regarded as a special case of the expectation-maximization (EM) algorithm. This leads to a general theoretical framework for turbo synchronization that allows to derive parameter estimation procedures for carrier phase and frequency offset, as well as for timing offset and signal amplitude. The proposed mathematical framework is illustrated by simulation results reported for the particular case of carrier phase and frequency offsets estimation of a turbo-coded 16-QAM signal.